Renal hyperfiltration is associated with a reduced incidence of hypertension in individuals younger than 70 - Hee-Jung Ha; Min Kyoung Kang; Jeong Hwa Kim; Youn-Hee Choi; Tae-Jin Song (Scientific Reports)
Abstract Although the connection between decreased kidney function and hypertension is commonly acknowledged, there is insufficient research examining the relationship between renal hyperfiltration (higher-than-normal estimated glomerular filtration rate (eGFR)) and the incidence risk of hypertension. Therefore, through a nationwide longitudinal study, our research aimed to explore the relationship between the eGFR and the incidence risk of hypertension in the general population. This research used the cohort records for the National Health Insurance Service in Korea, analyzing records from 1,873,550 individuals between the ages of 20 and 79 who underwent health check-ups between 2010 and 2011. The eGFR levels, determined by applying the 2009 Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation, were employed to evaluate the renal function. An incidence of hypertension was confirmed when a diagnosis of (primary or secondary) hypertension (International Classification of Diseases (ICD)-10 codes I10-I11) was noted at least once per year during outpatient or inpatient care with a prescription for antihypertensive medication or at least one more surpassing 140/90 mmHg from a health examination after the index date after excluding diagnosis of secondary hypertension. The mean age of subjects was 46.03 ± 11.24 years. The 411,029 (21.9%) hypertension cases were identified over a median follow-up of 9.53 years. In the multivariable Cox regression analysis, compared with the 5th decile, the 10th eGFR deciles (≥ 115.58 mL/min/1.73 m²) (hazard ratio (HR): 0.87, 95% confidence interval (CI)(0.85–0.88), p < 0.001) demonstrated a significant association with a reduced incidence of hypertension. Moreover, an eGFR exceeding 120 mL/min/1.73 m² was linked to a lowered likelihood of hypertension (HR: 0.78, 95% CI (0.76–0.80), p < 0.001) compared to normal eGFR levels (90 ~ 120 mL/min/1.73 m²). In contrast, in the subgroup analysis of ages over 70 years old, renal hyperfiltration was not associated with a reduced incidence of hypertension. In our study, renal hyperfiltration were associated with a reduced risk of hypertension, and this association was particularly significant in those younger than 70 years old. The association between renal hyperfiltration and a lower risk of hypertension incidence was likely to vary with age.